PERTANGGUNGJAWABAN PEMERINTAH TERHADAP EFEK SAMPING KEBIRI KIMIA TERHADAP TERDAKWA KEJAHATAN SEKSUAL - Michael Steven Ernanda; Hari Soeskandi (Gapenas Publisher, 2022)
Sexual crime against children is a crime that violates morals which has a very large impact on children who are a nation's asset whose existence is protected by law, it is appropriate if child predators are punished for criminal acts committed from an accountability for actions that tarnish the nation's moral values. Through Law of the Republic of Indonesia Number 17 Year 2022 and explicitly the mechanism of chemical castration is regulated in Government Regulation No. 70 of 2020 which is a form of care and protection for children who are vulnerable to the dangers of sexual crimes. Chemical castration has the potential for harmful side effects on the defendant's body as the person being executed, these harmful effects can arise as a result of the drugs or injections used while the effects are osteoporosis, fat accumulation, depression, diabetes and heart disease. From the side effects that endanger the life of the defendant, the government as the legislator of Government Regulation number 70 year 2020 which contains a void in legal norms should consider adding anticipatory action rules and actions that must be taken if the defendant gets side effects during or after chemical castration is carried out